2002
DOI: 10.1002/pola.10535
|View full text |Cite
|
Sign up to set email alerts
|

Telomerization of vinylidene fluoride with alkyl (or aryl) trifluoromethanethiosulfonates

Abstract: The photochemical‐induced telomerization of vinylidene fluoride (VDF) with cyclohexyl (or phenyl) trifluoromethanethiosulfonate (CF3SO2SR), leading to CF3(VDF)nSR telomers, where R stands for cyclohexyl or phenyl, is presented. These sulfurated transfer agents were synthesized by the reaction between sodium triflinate (CF3SO2Na) and disulfide in the presence of bromine. 19F NMR spectroscopy enabled an assessment of the average degrees of telomerization (DPn) of these telomers with a neat CF3 end group as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
3
30
1
Order By: Relevance
“…Besides, the usual VDF signals (−92, −113, and −116 ppm, assigned to normal and reverse VDF–VDF addition, respectively), the 19 F NMR spectra showed a quintet centered at −62 ppm. This quintet arises from the same 3 J FH and 4 J FF coupling constants that worth 10 Hz and is consistent with CF 3 –CH 2 –CF 2 – (Figure 1), as previously observed for VDF telomers obtained from the radical telomerization of VDF with CF 3 I34 or from the photopolymerization of VDF in the presence of CF 3 SO 2 SC 6 H 11 or CF 3 SO 2 SC 6 H 5 (both of them released a •CF 3 radical under UV radiation, Scheme ) 39. Actually, the absence of any signal at ≈ −83 ppm characteristic of CF 3 in CF 3 CF 2 ‐R confirms the regioselectivity of the addition of •CF 3 radical onto CH 2 site of VDF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the usual VDF signals (−92, −113, and −116 ppm, assigned to normal and reverse VDF–VDF addition, respectively), the 19 F NMR spectra showed a quintet centered at −62 ppm. This quintet arises from the same 3 J FH and 4 J FF coupling constants that worth 10 Hz and is consistent with CF 3 –CH 2 –CF 2 – (Figure 1), as previously observed for VDF telomers obtained from the radical telomerization of VDF with CF 3 I34 or from the photopolymerization of VDF in the presence of CF 3 SO 2 SC 6 H 11 or CF 3 SO 2 SC 6 H 5 (both of them released a •CF 3 radical under UV radiation, Scheme ) 39. Actually, the absence of any signal at ≈ −83 ppm characteristic of CF 3 in CF 3 CF 2 ‐R confirms the regioselectivity of the addition of •CF 3 radical onto CH 2 site of VDF.…”
Section: Resultsmentioning
confidence: 99%
“…The telomerization of VDF was reviewed5 and showed that many chain transfer agents (CTA) have been used. •CF 3 is an interesting30 radical that can be generated from various precursors: CF 3 X (X = I13, 31–34, Br35), bis(trifluoroacetyl) peroxide (CF 3 CO 2 ) 2 ,36, 37 CF 3 ‐paracyclophane,38 alkyl (or aryl) trifluoromethanethiosulfonates (CF 3 SO 2 SR)39 (Scheme ). Specific experimental (thermal or photochemical) conditions have been used for such CTA or initiators.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chambers et al67 used brominated telogens under γ rays or thermal initiation to produce telomers of various weight‐average molecular weights ( M w 's) by controlling the initial molar ratio of the reactants. Several investigations of the oligomerization13, 68 and cotelomerization69–72 of VDF and HFP have also been carried out. The first two studies13, 68 were initiated thermally (under dead‐end copolymerization), the third one69 was photochemically initiated, whereas the last ones70, 71 were initiated by peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…Successful telomerizations where the initiator generates a CF 3 • radical have also been reported. [37][38][39] Possible direct initiation was demonstrated using alcohols as poorly efficient telogens. 40 In the case of C-I cleavable telogens, it was observed that the telomerization yields mainly to the monoadduct and the addition of R F  radical occurs exclusively onto the CH 2 side of VDF, 3,[33][34][35]39 though one study showed that this addition could also occur onto the CF 2 side of VDF.…”
Section: Introductionmentioning
confidence: 99%